2024
DOI: 10.47104/ebnrojs3.v4i4.256
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers of Employing Electronic Exams as Perceived by Nursing Students and the Relation to their Satisfaction

Abstract: Context: Nowadays, during the COVID-19 pandemic, electronic exams are perceived as a fast-evolving assessment tool because of their accuracy and reliability. It provides relatively more accurate results and immediate feedback for students and instructors. Aim: To assess facilitators and barriers of employing electronic exams as perceived by nursing students and the relation to their satisfaction. Methods: A descriptive correlational research design was used to achieve the aim of this study. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of the present study clarified that, nearly two-thirds of the studied students had a higher satisfactory level regarding the electronic exam. These results were in accordance with Omran et al, (2022) (38) who assess facilitators and barriers of electronic exams by nursing students and reported that more than two-thirds of the nursing students had a higher level of satisfaction regarding electronic exams. In addition, this finding consistence with a study done by Donovan et al, (2019) (39) who evaluate the online vs. traditional course and revealed that more than four-fifth of students preferred electronic exam as a method of evaluation.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study clarified that, nearly two-thirds of the studied students had a higher satisfactory level regarding the electronic exam. These results were in accordance with Omran et al, (2022) (38) who assess facilitators and barriers of electronic exams by nursing students and reported that more than two-thirds of the nursing students had a higher level of satisfaction regarding electronic exams. In addition, this finding consistence with a study done by Donovan et al, (2019) (39) who evaluate the online vs. traditional course and revealed that more than four-fifth of students preferred electronic exam as a method of evaluation.…”
Section: Discussionsupporting
confidence: 91%